Administrative backbone of the international criminal justice - Jop, Artur (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The goal of this paper is to underline the necessity of a strong administrative backbone within the International Criminal Law regime. Often an overlooked phenomenon in the ICL, the administrative endeavours of various Tribunals provide not only an excellent ground for comparative analysis but also a fresh, fascinating perspective on the entirety of the administrative law. The depth to which it saturates other fields of law, and the very noble ideals behind this commonly disregarded field of law. Within this paper an introduction to the International Criminal system will be made, with emphasis on its various administrative realities, and further analysis of the function of the International Criminal Courts administrative branch as an example of excellence in the field.
Keywords: Administrative Law; Legal Theory; International Criminal Law; International Administrative Law